Improving service quality and commitment to the profession through strengthening Organizational Citizenship Behavior (OCB), job satisfaction and self-efficacy - Siti Utami, Ichwani; Notosudjono , Didik; Sunaryo , Widodo (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2024)
Abstract : This study aims to analyze the improvement of service quality and commitment to the profession through strengthening Organizational Citizenship Behavior (OCB), job satisfaction, and self-efficacy. Optimal service quality and commitment to the profession are key factors in improving organizational performance, especially in the public service and education sectors. OCB as an extra-role behavior carried out voluntarily by employees is expected to be a driving factor in improving service quality and commitment to the profession. In addition, high job satisfaction and strong self-efficacy also play an important role in strengthening OCB. This study uses a quantitative approach with a survey method on employees in the public service sector. The results of the study indicate that OCB, job satisfaction, and self-efficacy significantly contribute to improving service quality and commitment to the profession. The implications of this study are expected to provide insight for organizational management in developing performance improvement strategies by strengthening these factors.